Assistive listening devices for individuals with hearing impairment - Ekpete, Obutor Happiness (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This paper examined assistive listening devices for individuals with hearing impairment. Assistive listening devices (ALDs) play a vivacious role in enhancing communication for persons with hearing impairment. Several intervention methods and technologies, including assistive listening devices, hearing aids, auditory rehabilitation, cochlear implants, and personalized educational interventions, are explored as means to address an individual's specific needs. This paper delves into the multifaceted realm of hearing impairment, addressing its prevalence, categorization, diagnostic procedures, and management strategies. It underscores the crucial role of comprehensive assessment conducted by audiologists and otolaryngologists in guiding treatment decisions. It emphasizes the significance of ALDs in addressing the obstacles encountered by those with hearing impairment. Furthermore, the paper highlights the significance of increased awareness and early intervention processes to foster inclusivity for individuals with hearing impairment and alleviate the impact of hearing impairment.